The evaluation of endurance improvement in the transition period - Raiola, G.; D'Isanto, T.; D'Elia, F.; Altavilla, G. (Physical Education, Sport and Kinetotherapy Journal, 2019)
Soccer is a sport with wide popularityin Italy. The aim of the study was to analyse and evaluate the performance decrease or improvement intwo groups of 12 malesoccer players aged 13-14 years (group A and group B). Group A continues the training sessions during the transition period, while group B does not continue the workouts.The study method is experimental.The tests applied to young soccer players are easy to administer and are intended to investigate two different characteristics of endurance, namely general and specific endurance.The data were collected over eight weeks (during the transition period). All the collected data were expressed as average ± SD for height, weight, body mass index (BMI) and the Cooper test.The statistical analysis of data involves using the Student'st-Test to assess the performance ofthe two groups in the transition period (June-September) and between the two groups in September. The significant differences were set at p < 0.05. The results show that there is a significant difference between the two groups in September. For group B (that does not continue the training during the transition period), there is nosignificant difference, while for group A (that continues the training during the transition period), there is a significant difference. The analysis and evaluation of the performance decrease or improvement allow coaches to monitor the training process and design the training load for effective performance.